1993
DOI: 10.1073/pnas.90.12.5823
|View full text |Cite
|
Sign up to set email alerts
|

Serum "big insulin-like growth factor II" from patients with tumor hypoglycemia lacks normal E-domain O-linked glycosylation, a possible determinant of normal propeptide processing.

Abstract: The insulin-like growth factor II (IGF-II) gene is overexpressed in many mesenchymal tumors and can lead to non-islet-cell tumor hypoglycemia (NICTH). ProIGF-II consists of the 67 aa of IGF-II with a carboxyl 89-aa extension, the E domain. A derivative of proIGF-II containing only the first 21 aa of the E domain [proIGF-II-(E1-21)] has been isolated by others from normal serum and has 0-linked glycosylation. We found that the "big IGF-II" of normal serum, as detected by an RIA directed against residues 1-21 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 23 publications
1
63
1
Order By: Relevance
“…Post-translational processing begins with cleavage of the signal peptide to yield pro-IGF2 (1-156). This is followed by O-linked glycosylation of the 89-residue E-domain that may promote further processing (Daughaday et al 1993). Pro-IGF2 then undergoes sequential proteolysis to mature IGF2 (1-67) that lacks the E-domain.…”
Section: Igf2mentioning
confidence: 99%
See 1 more Smart Citation
“…Post-translational processing begins with cleavage of the signal peptide to yield pro-IGF2 (1-156). This is followed by O-linked glycosylation of the 89-residue E-domain that may promote further processing (Daughaday et al 1993). Pro-IGF2 then undergoes sequential proteolysis to mature IGF2 (1-67) that lacks the E-domain.…”
Section: Igf2mentioning
confidence: 99%
“…The reason for impaired proteolytic processing of pro-IGF2 is unclear but recent studies have suggested mechanisms. First, processing may fail because of the absence of glycosylation (Daughaday et al 1993). Secondly, the quantity of pro-IGF2 produced may overwhelm the proteolytic capacity of the tumour cells (Zapf 1993).…”
Section: Mechanism Of Hypoglycaemiamentioning
confidence: 99%
“…Such an event does not occur for two reasons: 1) formation of 150 kDa (ALS-IGFBP-3/IGFBP-5-IGF) complexes that cannot cross the vascular endothelial cell barrier allow high concentrations of IGFs to accumulate in the blood without risk of hypoglycemia; 2) much of the IGF in the remaining 40-50 kDa complex is bound to inhibitory IGFBPs, and the IGFs in this complex are not bioavailable unless this complex is broken down (Rajaram et al 1997). The importance of IGFBPs in preventing the insulin-like effects of IGFs is evident from studies involving non-islet cell tumor hypoglycemia (NICTH), in which hypoglycemia is seen in the absence of detectable insulin because of the overproduction of partially processed biologically active IGF-II by mesenchymal tumors (Daughaday et al 1993, Zapf 1994. The state of hypoglycemia found in patients with NICTH is associated with an increase in the serum concentration of pro IGF-II, a decrease in the circulating concentration of the 150 kDa complex, and a corresponding increase in the circulating concentration of 50 kDa complex (Daughaday et al 1993, Zapf 1994, Rajaram et al 1997.…”
Section: Igfbps Prevent the Insulin-like Activity Of Igfsmentioning
confidence: 99%
“…In addition to mature IGF-II, two ''big'' variants, IGF-II (1-87) and IGF-II (1-104), have been identified in human and bovine serum (10)(11)(12)(13). They are 11-17 kDa in size, contain 87 or 104 amino acids, respectively, and differ in glycosylation (10)(11)(12)(13)(14). It has been suggested that big IGF-II is biologically active but may have different activity in tumor cells when compared with mature IGF-II (15).…”
mentioning
confidence: 99%